Acid–base reaction of a super‐photoacid with a cooperative amide hydrogen‐bonded chain. (25th January 2022) - Choi, Ye‐Jin; Kim, Heesu; Kwon, Oh‐Hoon
Abstract: The excited‐state proton transfer (ESPT) of the strong photoacid, N ‐methyl‐7‐hydroxyquinolium (NM7HQ + ), was studied in the presence of N ‐methylbenzamide (NMB) as a base in the aprotic polar solvent, acetonitrile. According to the Benesi–Hildebrand relation, it was revealed that the hydrogen (H)‐bonded complex of NM7HQ + and NMB exists in the ground state in a 1:1 stoichiometry with the association constant of 22.2 ± 1.7 M −1 . The fluorescence quenching of the 1:1 complex was observed to follow the Stern–Volmer relation with the molecularity of one for NMB indicating that the ESPT of NM7HQ + occurs with the H‐bonded chain of two NMB molecules. Our study highlights the cooperative nature of H‐bonding in the chemical reactivity of amide in acid–base reactions as has already been reported for alcohol. Abstract : The excited‐state proton transfer of a strong photoacid was found to occur to a hydrogen‐bonded amide dimer. For the bind step of the acid–base reaction, an additional amide molecule clusters to the dimer to dissociate the acid–base encounter complex. The study reports the cooperative nature of H‐bond clustering that enhances the chemical reactivity of amides in acid–base reactions.